2013
DOI: 10.1007/s00267-013-0108-7
|View full text |Cite
|
Sign up to set email alerts
|

Land Management Versus Natural Factors in Land Instability: Some Examples in Northern Spain

Abstract: The objective of this work is to test a hypothesis formulated on the basis of former results which considers that there might be a ‘‘global geomorphic change,’’ due to activities related to land management and not determined by climate change, which could be causing an acceleration of geomorphic processes. Possible relationships between some geomorphic processes related to land instability (landslides or sediment generation) and potential triggering factors are analyzed in study areas in northern Spain. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 56 publications
2
25
0
2
Order By: Relevance
“…They were used to estimate sediment generation within the lakes' basins and their consequent sediment supply. As expected from previous results (Bonachea et al, 2010;Bruschi et al, 2013), the latter data yielded significantly higher potential sedimentation rates than the former.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…They were used to estimate sediment generation within the lakes' basins and their consequent sediment supply. As expected from previous results (Bonachea et al, 2010;Bruschi et al, 2013), the latter data yielded significantly higher potential sedimentation rates than the former.…”
Section: Methodssupporting
confidence: 89%
“…In general, human-induced geomorphic changes have led to increasing surface geologic processes, particularly after the middle of the 20th century, coinciding with the sharp increase in human activities and their effects known as the 'Great Acceleration' (Steffen et al, 2004(Steffen et al, , 2011(Steffen et al, , 2015. The Great Acceleration represents a 'great geomorphic acceleration' (Bruschi et al, 2013;Bruschi et al, 2012a,b;Hurtado et al, 2012), which can be problematic but beneficial as well.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in densely-populated regions, the impacts of humans on the environment contribute significantly to the initiation and reactivation of landslides [40,42,43,44,45,46]. Thus, landslide episodes usually are serious in developing countries where the environment protection and management are hardly sustainable [43,45,47]. We have found that landslide episodes might significantly concentrate in Southwest China, which is in line with previous studies [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The Delphi method, one of the important methods used in this study, is an effective tool for reaching a consensus value; however, it cannot provide objective weights. Additionally, only the climate conditions are changed in the future vulnerability assessment even though damage can have a significantly stronger dependence on other conditions such as land surface modification (Bonachea et al 2010;Bruschi et al 2013). This limitation is attributed to the lack of future environmental and socioeconomic data.…”
Section: Discussionmentioning
confidence: 99%